Reduced renal function is associated with prolonged hospitalization in frail older patients with non-severe pneumonia - Kanno, Atsuhiro; Kimura, Ryo; Ooyama, Chika; Ueda, Juri; Miyazawa, Isabelle; Fujikawa, Yuko; Sato, Shigeru; Koinuma, Nobuo; Ohara, Takahiro; Sumitomo, Kazuhiro; Furukawa, Katsutoshi (Frontiers in Medicine, 2022)
Objective: Pneumonia is a disease with high morbidity and mortality among older individuals in Japan. In practice, most older patients with pneumonia are not required ventilatory management and are not necessarily in critical respiratory condition. However, prolonged hospitalization itself is considered to be a serious problem even in these patients with noncritical pneumonia and have negative and critical consequences such as disuse syndrome in older patients. Therefore, it is essential to examine the factors involved in redundant hospital stays for older hospitalized patients with non-severe pneumonia, many of whom are discharged alive. Method: We examined hospitalized patients diagnosed with pneumonia who were 65 years and older in our facility between February 2017 and March 2020. A longer length of stay (LOS) was defined in cases in which exceeded the 80th percentile of the hospitalization period for all patients was exceeded, and all other cases with a shorter hospitalization were defined as a shorter LOS. In a multivariate logistic regression model, factors determining longer LOSs were analyzed using significant variables in univariate analysis and clinically relevant variables which could interfere with renal function, including fasting period, time to start rehabilitation, estimated glomerular filtration rate (eGFR), the Quick Sequential Organ Failure Assessment (qSOFA) score of 2 or higher, bed-ridden state. Results: We analyzed 104 eligible participants, and the median age was 86 (interquartile range, 82-91) years. Overall, 31 patients (30.7%) were bed-ridden, and 37 patients (35.6%) were nursing-home residents. Patients with a Clinical Frailty Scale score of 4 or higher, considered clinically frail, accounted for 93.2% of all patients. In multivariate analysis, for a decrease of 5 ml/min/1.73m2 in eGFR, the adjusted odds ratios for longer LOSs were 1.22 (95% confidence interval, 1.04-1.44) after adjusting for confounders. Conclusion: Reduced renal function at admission has a significant impact on prolonged hospital stay among older patients with non-severe pneumonia. Thoughtful consideration should be given to the frail older pneumonia patients with reduced renal function or with chronic kidney disease as a comorbidity at the time of hospitalization to prevent the progression of geriatric syndrome associated with prolonged hospitalization.